A Systematic Review and Meta-analysis of Race/Ethnicity Reporting in Women's Health Research [A54]. (May 2022) - Michel, Lindsey; Josama, Pascale; Stern, Rachel; Chudnoff, Scott
Abstract : INTRODUCTION: Health disparities are well documented in the field of obstetrics and gynecology as highlighted by the current maternal mortality crisis. While research is pivotal to understanding the underlying causes of these disparities, minorities have traditionally been underrepresented in clinical studies. The objective of this study was to investigate trends in racial and ethnic reporting in women's health research. Our secondary objective was to examine changes in reporting over the last decade. METHODS: A systematic review of original research articles from three high-impact obstetrics and gynecology journals (American Journal of Obstetrics & Gynecology (AJOG) Fertility & Sterility, and Obstetrics & Gynecology) was performed. Research articles were screened for the reporting of race/ethnicity and method of documenting data. Data were collected at 2- year timepoints, 2009 and 2019, for comparison. RESULTS: A total of 1, 440 articles (AJOG n=514, Fertility & Sterility n=551, and Obstetrics & Gynecology n=375) were included and analyzed. Overall, race and ethnicity data were reported in 37.5% and 7.7% of research articles respectively. Only 2.2% of articles included both race and ethnicity data. There was a significant difference in the reporting of race (32.6% in 2009 vs. 54.8% in 2019, P <.05) and ethnicity (6.4% in 2009 vs. 10.1% in 2019, P <.05) data over the 10-year time span. CONCLUSION: The reporting of race/ethnicity is inconsistent and often lacking in women's health literature. When reported, there is significant heterogeneity in how demographic data is documented. Although there have been some improvements in the last decade, standardized reporting could allow clinicians to be more informed of the generalizability of novel research findings.